Desenvolvimento e teste de um modelo QM/MD/PCM para descrever solvatação e reações em solução usando resposta linear. - Guilherme Ferreira de Lima (2010)
The methodology development for describing the solvent effect remains as an important area in theoretical chemistry research. Explicit solvent models, in general, provide reasonable results; however, their computational effort is much larger. On the other side, continuum models are computationally faster than explicit models but they are highlyparameterized and they do not describe the solute-solvent specific interactions. Continuum models are efficient for neutral molecules, however, their ability for describing ionic species are limited.In this work, we applied a new method for estimating the solvation free energy. In this model the solvent is partitioned in two regions. In the shell closer to the solute, explicit solvent molecules were used and the solute-solvent interaction is obtained through the linear response approach. The second shell is described by a continuum model. The electrostatic contribution of the solvation free energy for ammonium, hydroxide, hydronium and cyanide were estimated using C-SCC-DFTB/molecular dynamics simulation results. The values havebeen estimated as average of the calculations performed on snapshots produced by the molecular dynamics. The solvation free energy was calculated using structures with different number of explicit water molecules in order to assess the convergence of the method. Theinteraction between the solute and the explicit solvent molecules was estimated at the PBE/6- 31+G** level of theory and the long range effects were estimated by PCM (polarizable continuum model). The results show that the method converges with approximately 32 water molecules explicitly treated. The solvation free energy for ammonium and hydronium ion converged to -73 and -90 kcal mol-1, respectively. These results are in good agreement with the experimental values. For hydroxide and cyanide, the solvation free energy converged to -95 and -69 kcal mol-1 and these values correspond to 80% of the experimental value. We attributed this performance of the method to the first approximation in the linear response formalism. The main advantage of the method is to be convergent and to take into account the solvent dynamics. Furthermore it is not dependent of ions parameters in the calculations usingthe continuum models. We applied this model to describe the hydroxylamine in water and our results pointed out that neutral species is about 5 kcal mol-1 more stable than the respective zwitterionic species.